Effect of internal stress on cyclic fatigue failure in K3 - Jun-Young Kim; Jin-Woo Kim; Kyung-Mo Cho; Se-Hee Park (Korean Academy of Conservative Dentistry, 2012)
Objectives This study aimed to evaluate the relationship between the cyclic fatigue of a K3 file and internal stress intentionally induced until the activation of the auto-stop function of the torque-controlled motor. Materials and Methods K3 (Sybron Endo) .04 and .06 taper, size 25, 30, 35, 40 and 45 were used in this study. To give the internal stress, the K3 files were put into the .02 taper Endo-Training-Bloc (Dentsply Maillefer) until the activation of the auto-stop function of the torque-controlled motor. The rotation speed was 300 rpm and torque value was 1.0 N·cm. K3 were grouped by the number of induced internal stress and randomly distributed to 4 experimental groups (n = 10, Stress 0 [control], Stress 1, Stress 2 and Stress 3). For measuring the cyclic fatigue failure, the K3 files were worked against a sloped glass block and time for file separation was recorded. Data was statistically analyzed Statistical analyses were performed using two-way ANOVA and Duncan post-hoc test at p < 0.05 level. Results Except .04 taper size 30 in Stress 1 group, there were statistically significant differences in time for file separation between control and all experimental groups. K3 with .04 taper showed higher cyclic fatigue resistance than those of .06 taper. Conclusion In the limitation of this study, the cyclic fatigue of the K3 file was influenced by the accumulated internal stress from use until the auto-stop function was activated by the torque-controlled motor. Therefore, clinicians should avoid the reuse of the K3 file that has undergone auto-stops.